RATIONAL MANAGEMENT OF PARKINSON’S DISEASE - Yin Yen, Mun; Tirtayasa, Ketut; Sutjana, Dewa Putu (Bali Journal of Medical and Health Sciences, 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 P a rkinson ’ s dise a se is a c h r onic a nd p r o g r e s s ive n e u r od e g e n e r a t i ve dise a se whi c h is c h a ra c te r i z e d b y mo t or a nd no n - mo t or s y mp t oms. The mo t or s y mp t o ms whi c h a r e a lso known a s ca rdin a l f e a tu r e s a re r e st i n g tr e mor, b r a d y kinesia, r i g id i t y a nd p ostur a l ins t a bi l i t y . The e t i olo g y is un k nown in most ca s e s but th e re a re findi n g s that r e late Par kinson ’ s dise a se to the g e n e t i c s a nd e nvi r onment a l f a c tors. The c l i nic a l c ourse of P a rkinson ’ s dise a se v a ri e s f r om p a t i e nt to p a t i e nt. L e vodo p a is st i ll the ma i n the ra p y o f th i s dise a se a l t hou g h it l ea ds to m otor c omp l ic a t i ons a s the dise a se pr o g re sses. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}